The Architecture of Evil: H. P. Lovecraft's 'The Dreams in the Witch House' and Shirley Jackson's The Haunting of Hill House. Issue 3 (December 2018) - Matek, Ljubica
Abstract : This paper proposes that H. P. Lovecraft's 'The Dreams in the Witch House' (1932) and Shirley Jackson's The Haunting of Hill House (1959) embody the Gothic idea of subversion through their use of space. Specifically, both texts are set in a house that is shaped according to a scale unknown and repulsive to humans, suggesting that the architecture of evil is out of scale literally and metaphorically. Walter Gilman's room in the Witch House is strangely shaped and represents a passage into a parallel world which Gilman, a mathematician firmly set into the world of scale, first believes to exist only in dreams. Similarly, the interior of the Hill House is off centre and disjointed. People get physically lost as the rooms are set in strange concentric circles which defy traditional architecture; more importantly, characters' subjectivity is consumed and appropriated by the house. By depicting protagonists as scientists deeply invested in the research of the occult, both Jackson and Lovecraft juxtapose science, which is marked by taxonomies, systems, and scales, with entities and rituals that transcend scalable knowledge. As their projects fail, the perceived harmony and knowability of life is revealed as false. The collapse of scale in both texts unsettles the reader, as it suggests that evil refuses to comply and be contained within a specific human-designed system of measurement or value. With this, the texts confirm the Gothic genre's countercultural position within the literary canon.